An ultrasonic feeding mechanism for continuous aerosol generation from cohesive powders. Issue 3 (4th March 2019) - Pokharel, Lekhnath; Parajuli, Prashant; Li, Li; Chng, Ewe Jiun; Gopalakrishnan, Ranganathan
Abstract: The dispersion of dry, cohesive micro- and nanosized powders has wide applications ranging from medical and environmental science to manufacturing technology. Being able to disperse the dry powder at a stable concentration over periods of time (∼hour to several hours) is challenging to achieve, which we attempt to address with a novel dry powder dispersion technology. A portable, cost effective and simple dry powder dispersion device that uses ultrasonic energy for continuous feeding of aerosol particles to a de-agglomeration device is developed and tested with commercially available powders. The study is performed using 5 µm polyamide powder and rutile TiO2 powders of 500, 100, and 30 nm mean size of primary particles. The ultrasonic dispersion device proved to be able to disperse all of these powders, which represent low-density material to high-density metal oxides, with stable concentration over periods that extend to an hour. From aerosol measurements to obtain the size distribution of various size particles, it is seen that the highly agglomerated powder particles are not easy to de-agglomerate as we go to the lower (nominal) sized powders because of the stronger inter-particle adhesion forces between nanoparticles compared to microparticles. The scanning electron microscopy (SEM) images of particles in their native powder state and those collected after the dispersion showed significant difference in the agglomeration of the powder particles, which suggests partial success of the turbulent jet de-agglomeration employed. Copyright © 2019 American Association for Aerosol Research